2016
DOI: 10.1016/j.pmedr.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical activity, sleep duration and depressive symptoms in older adults: The English Longitudinal Study of Ageing (ELSA)

Abstract: Research to date suggests that physical activity (PA) is associated with distinct aspects of sleep, but studies have predominantly focused on sleep quality, been carried out in younger adults, and have not accounted for many covariates. Of particular interest is also the reported relationship between physical activity and depression in older adults and as such, their associations with sleep duration. Here we examine the cross-sectional relation between physical activity and sleep duration in a community-dwelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 23 publications
5
41
0
2
Order By: Relevance
“…In the present research, we have showed that the high intensity exercise program was capable to improve sleep quality, quality of life (social domain and psychological domain) and reduce anxiety levels of the subject (see Table 1). It is known that alcoholic subjects may develop sleep quality problems and this is associated with depression (Garfield, Llewellyn, & Kumari, 2016) and negative impacts on physical and mental health (da Silva et al, 2016). Importantly, studies have reported improved sleep quality for those who regularly practice exercise (Driver & Taylor, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In the present research, we have showed that the high intensity exercise program was capable to improve sleep quality, quality of life (social domain and psychological domain) and reduce anxiety levels of the subject (see Table 1). It is known that alcoholic subjects may develop sleep quality problems and this is associated with depression (Garfield, Llewellyn, & Kumari, 2016) and negative impacts on physical and mental health (da Silva et al, 2016). Importantly, studies have reported improved sleep quality for those who regularly practice exercise (Driver & Taylor, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The frequencies of responses for each of the four indexed catagorise [31] of physical activity were calculated at each assessment time-point. Prevalence of the four different physical inactivity levels with 95% confidence intervals (CI) were calculated for each of the three assessment phases.…”
Section: Discussionmentioning
confidence: 99%
“…For each type of activity, participants responded either as being: very active (more than once a week), active (once a week), moderately active (one to three times per month), and inactive (hardly ever/never). We derived a summary index of physical activity by summing responses to the three physical activity items once dichotomized around the frequency cut-point of once a week or more often, as described by Garfield et al [31]. Through this, physical activity was analyses as (1) sedentary (mild exercise one to three times a month, no moderate or vigorous activity); (2) low (mild, but no vigorous activity at least once a week); (3) moderate (moderate activity more than once a week, or vigorous activity between once a week to one to three times a month); and (4) high (heavy manual work or vigorous activity more than once a week).…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity participation was determined through the self‐reported ELSA physical activity questionnaire (ELSA‐PAQ) (Hamer, Molloy, de Oliveira, & Demakakos, ). Participants were asked how often they engaged in vigorous, moderate or mild physical activity (Demakakos, Hamer, Stamatakis, & Steptoe, ; Garfield, Llewellyn, & Kumari, ). This method has been used to determine the level of physical activity participation undertaken by older people (Demakakos et al, ; Garfield et al, ), and has demonstrated excellent convergent validity within this population (Hamer et al, ).…”
Section: Methodsmentioning
confidence: 99%